2006
DOI: 10.1111/j.1467-8306.2006.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Realism and Religion: Objectivity and the Insider/Outsider Problem

Abstract: This article uses the insider/outsider problem in the study of religion and a critical realist interpretation of objectivity to discuss two dialectics present in geography of religion literature: geography of religion versus religious geography, and politics versus poetics. Recent developments in critical realism include a ''spiritual turn'' in which critical realism as both a metaphilosophy and a method is applied to religious thought. A critical realist understanding of objectivity can effectively address te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…In this next section, using ANT concepts including human and nonhuman actors, changes to entrenchment, and nodal actors, I show how reflexive research design requires consideration of relations and relationships at all points in the research project. As I was doing field work, I aimed to be genuine, to be myself, in relationships, but I also knew that issues of insider–outsiderness inherent in ethnographic research meant, as geographers have shown, that I was both ‘in’ and ‘out’ of the field simultaneously (Nast 1994; Ferber 2006). Fine calls this ‘working the hyphen’ (1994, 72) – being in the between of different social places.…”
Section: Relations With and Relationships In The Fieldmentioning
confidence: 99%
“…In this next section, using ANT concepts including human and nonhuman actors, changes to entrenchment, and nodal actors, I show how reflexive research design requires consideration of relations and relationships at all points in the research project. As I was doing field work, I aimed to be genuine, to be myself, in relationships, but I also knew that issues of insider–outsiderness inherent in ethnographic research meant, as geographers have shown, that I was both ‘in’ and ‘out’ of the field simultaneously (Nast 1994; Ferber 2006). Fine calls this ‘working the hyphen’ (1994, 72) – being in the between of different social places.…”
Section: Relations With and Relationships In The Fieldmentioning
confidence: 99%
“…We are not the first to dwell on this issue. Debates surrounding the observer/believer, insider/outsider and poetic/political distinction have dominated social scientific attempts to study religion (McCutcheon 1999), and have recently been rehearsed by geographers (Ferber 2006; Kong 2001). Some geographers have attempted a kind of faith‐based reflexivity, seeking to narrate the linkages between a personal confession of religious faith and professional status, including reflections upon belonging, place, suffering and memory (Cloke 2004; Megoran 2004; Olliver 1989; Pacione 1990; Slater 2004; Wallace 1978).…”
Section: F/00144/u: Stories From a Leverhulme Trust Research Projectmentioning
confidence: 99%
“…Entre otros autores, destacan los trabajos de Morinis, 1983;Esteve, 2002;Tilson, 2005;Andrés y Espejo, 2006;Brace et al, 2006;Buttimer, 2006;Cànoves, 2006;Ferber, 2006;Ivakhiv, 2006;Blackwell, 2007;Collins-Kreiner, 2010;Cànoves y Blanco, 2011;Lois y López, 2012;Millan et al, 2012;Shinde, 2012;Maddrell y della Dora, 2013;Olsen, 2013;Wilson et al, 2013;Cànoves et al, 2014;Cebrián y García, 2014;Cors, 2014;López Palomeque y Font, 2014;Pardellas y Padin, 2014;Uriely et al, 2015;Cànoves y Prat, 2016;Llurdés, 2016. Por otra parte, también se está modificando la actitud de los residentes hacia los turistas, teniendo en cuenta, que una actitud es "un estado mental de disposición para responder que ejerce una influencia directa sobre la conducta" (Royo y Ruiz, 2009). Entre los factores más influyentes en las actitudes de los residentes hacia el turismo, se encuentran fundamentalmente dos: el tipo y grado de interacción entre los residentes y visitantes y la importancia de la actividad turística en el territorio (Murphy, 1983).…”
Section: Introductionunclassified